2001
DOI: 10.1016/s0923-1811(00)00123-7
|View full text |Cite
|
Sign up to set email alerts
|

Differential phosphorylation of mitogen-activated protein kinase families by epidermal growth factor and ultraviolet B irradiation in SV40-transformed human keratinocytes

Abstract: ELSEVIER, Nakamura, S; Takahashi, H; Kinouchi, M; Manabe, A; Ishida-Yamamoto, A; Hashimoto, Y; Iizuka, H, JOURNAL OF DERMATOLOGICAL SCIENCE, 25(2), 139-149, 2001. authorSV-40 transformed human keratinocytes (SVHK cells) were stimulated with epidermal growth factor (EGF)2 and ultraviolet B (UVB) irradiation. Following the stimulation, cell growth, apoptosis, and the activities of mitogen-activated protein (MAP) kinase families were analyzed. EGF (100ng/ml) increased SVHK cell number compared with control cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
13
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 42 publications
6
13
0
Order By: Relevance
“…Our data support the contention that MAP kinase activation, specifically of JNK family members, is related to protection against apoptosis (3,29,37,42,54). There is a growing consensus that if any correlation exists between activation of MAP kinases and protection or induction of apoptosis, it is stimuli and/or cell type dependent (15,22,36,52).…”
Section: Discussionsupporting
confidence: 87%
“…Our data support the contention that MAP kinase activation, specifically of JNK family members, is related to protection against apoptosis (3,29,37,42,54). There is a growing consensus that if any correlation exists between activation of MAP kinases and protection or induction of apoptosis, it is stimuli and/or cell type dependent (15,22,36,52).…”
Section: Discussionsupporting
confidence: 87%
“…These results are consistent with another report by Gunn-Moore et al, in which it was described that ERK inhibition had no significant effect on the insulin-or brain-derived neurotrophic factor-induced survival of cerebellar granule cells (GunnMoore et al, 1997). Similarly, it was reported by Nakamura et al (Nakamura et al, 2001) that UVB-irradiation induced significant increase in the phosphorylation of p38 MAPK, but only a slight increase of ERK phosphorylation, moreover, UVB-induced cell death was not significantly affected by PD98059. These results are in accordance with the findings described here and suggest that UVB-induced apoptosis in keratinocytes is not mediated by the activation of ERK signaling pathway.…”
Section: Erk Phosphorylation Is Not Involved In Uvb-induced Apoptosissupporting
confidence: 78%
“…Many reports indicate that UVB stimulates JNKs, p38 kinase, and ERKs and activates AP-1. As with the data related to UVA exposure, there are variations in responses depending on cell type and exposure dose (87,95,(155)(156)(157). Some examples of the discrepancies are highlighted.…”
Section: Uvb and Mapk Signalingmentioning
confidence: 98%
“…However, these actively proliferating cells had unusually high steady-state levels of ERK activity that were attributed to autocrine production of EGFR ligands. Another group showed that UVB (4000 J/m 2 ) stimulated the phosphorylation of p38 kinase and JNKs, but not ERKs, and that p38 kinase appeared to mediate apoptosis induced by UVB (156). Thus, as with UVA-induced signaling, UVB exposure stimulates cell type-specific signaling.…”
Section: Uvb and Mapk Signalingmentioning
confidence: 99%